Profiles of historical loss and childhood trauma as predictors of mental and cardiometabolic health in American Indian adults - Neha A. John-Henderson; Annie T. Ginty (Elsevier, 2023)
Cardiometabolic disease and mental health conditions are two major contributors to persistent inequities in health and life expectancy for American Indian adults. The atrocities associated with European colonization are linked to intergenerational psychological and emotional wounding (i.e., historical trauma) and high incidence of childhood trauma. Prior work has examined the independent relationships of childhood trauma and thoughts about historical loss with cardiometabolic and mental health in American Indians. In the current work, we used a data-driven approach to identify profiles of childhood trauma and frequency of thoughts about historical loss, and then examined how these profiles related to cardiometabolic and mental health in a sample of American Indian adults from across the United States (N = 727). We found that a profile characterized by high levels of childhood trauma and high frequency of thoughts about historical losses was associated with the greatest risk for mental health conditions. The profile characterized by the highest levels of childhood trauma and by moderate frequency of thoughts about historical losses was associated with the largest risk of cardiometabolic conditions. The findings represent an important first step towards understanding how childhood trauma and thoughts about historical loss may simultaneously inform enduring inequities in American Indian health.